2021
DOI: 10.3390/cancers13051031
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis Inhibitors for Colorectal Cancer. A Review of the Clinical Data

Abstract: Since the late 1990s, therapy for metastatic colorectal cancer (mCRC) has changed considerably, and the combination of doublet or triplet chemotherapy and a targeted agent are now routinely used. The targeting of angiogenesis, the development of new blood vessels, represents a key element in the overall treatment strategy. Since the approval in 2004 of the first anti-angiogenetic drug, multiple agents have been approved and others are currently under investigation. We present an overview of the recent literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 94 publications
0
25
0
Order By: Relevance
“…Both blood and lymphatic structures are lined with endothelial cells that communicate with the extracellular environments [ 28 ]. Angiogenesis and lymphangiogenesis often occur pathological conditions such as inflammation, tissue injury, and tumor growth [ 29 ], and both of them are responded to multiple inducers or inhibitors [ 19 , 30 , 31 ]. A number of studies have been reported that factors involved in angiogenesis also have an effect on lymphangiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Both blood and lymphatic structures are lined with endothelial cells that communicate with the extracellular environments [ 28 ]. Angiogenesis and lymphangiogenesis often occur pathological conditions such as inflammation, tissue injury, and tumor growth [ 29 ], and both of them are responded to multiple inducers or inhibitors [ 19 , 30 , 31 ]. A number of studies have been reported that factors involved in angiogenesis also have an effect on lymphangiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The first anti-angiogenic agent entering the clinic for the treatment of mCRC has been bevacizumab, a humanized monoclonal antibody anti-VEGF-A which binds circulating VEGF-A and blocks the interaction with its cell surface receptors (VEGFR1 and 2), thus reducing microvascular growth and inhibiting the blood supply to the tumor tissues [140] . In recent years the development of anti-angiogenic agents has increased, leading to the addition to of aflibercept (second-line treatment for advanced CRC) and regorafenib (in patients with mCRC who have already received chemotherapy and other targeted therapies).…”
Section: Resistance To Anti-angiogenic Therapymentioning
confidence: 99%
“…Regorafenib is multi-kinase inhibitor targeting angiogenic, stromal, and oncogenic receptor tyrosine kinase that shows strong anti-angiogenic activity due to its dual targeted VEGFR2-TIE2 tyrosine kinase inhibition. In addition, other anti-angiogenic drugs are in preclinical and clinical phase I-III studies [ 141 ] .…”
Section: Resistance To Targeted Therapymentioning
confidence: 99%
“…Recently, we demonstrated that about 50% of BRAF and RAS wt CRC sphere cells (CR-CSphCs) are resistant to cetuximab treatment due to high expression levels of CD44v6 [11,17]. Many other therapeutic strategies, including anti-angiogenic drugs and Met pathway and immune checkpoint inhibitors, are currently under evaluation for managing CRC treatment [2,[18][19][20][21]. Another common mechanism of resistance to standard and targeted therapies is gene amplification/overexpression [22][23][24].…”
Section: Introductionmentioning
confidence: 99%